2021
DOI: 10.1177/1440783321998428
|View full text |Cite
|
Sign up to set email alerts
|

Australians’ divergent opinions about Islam and Muslims

Abstract: Using data from a random stratified sample of people over 18 years of age residing in Australia, this article examines participants’ opinions of the Islamic faith independently of their opinions of Muslim people. Earlier studies have not made the nuanced distinction between opinions about Islam as a religion and opinions about Muslims as people. Theoretical approaches suggest that there is a difference in the opinions non-Muslims have of Muslims and their religion. The non-Muslim Australians we surveyed have v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…However, there have been few studies of non-Muslim Australians' attitudes towards Muslims. We will focus briefly on the European research because we know that Europeans are more concerned about the presence of Muslims than they are about the Islamic faith (Erdenir, 2010), but in Australia it is the opposite (Ewart et al, 2022). We also summarise some research from New Zealand because it is close to Australia and also has a very small proportion of Muslims in its population.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been few studies of non-Muslim Australians' attitudes towards Muslims. We will focus briefly on the European research because we know that Europeans are more concerned about the presence of Muslims than they are about the Islamic faith (Erdenir, 2010), but in Australia it is the opposite (Ewart et al, 2022). We also summarise some research from New Zealand because it is close to Australia and also has a very small proportion of Muslims in its population.…”
Section: Literaturementioning
confidence: 99%
“…In the aforementioned studies, researchers have not specifically separated Muslims from their faith when surveying non-Muslim Australians about their attitudes and prejudices towards Muslims. A study we undertook with a colleague (Ewart et al, 2022 ) reveals an important distinction between non-Muslim Australians' attitudes towards Muslims and Islam. Using data from a random, stratified survey, the 2017 National Social Survey of Australians, we found that non-Muslim Australians hold more favourable views of Muslims than they do of Islam.…”
Section: Australiamentioning
confidence: 99%
“…Recent racism research has also given considerable attention to Muslim Australians. A national survey showed that 20% of non-Muslim participants stated that they would rather not live in a place 'where there are Muslims' [35], while another study found unfavourable opinions about Muslims and about Islam among 12% and 27% of participants, respectively [36]. In other surveys, as many as 63% and 56% of participants were concerned about marrying someone of a Muslim faith [23,37].…”
Section: Previous Studiesmentioning
confidence: 99%
“…The longitudinal Building a New Life in Australia (BNLA) study (2013)(2014)(2015)(2016)(2017)(2018) examined the settlement experiences of humanitarian migrants, and included measures of discrimination due, for example, to ethnicity, religion or skin colour, across settings, as well as responses to racism. Several studies around this time focused on racism against Muslims and especially on Islamophobia, including the Being Muslim in Australia (BMA) survey, and other national surveys Ewart et al, 2021;Gravelle, 2021). Likewise, the Australian Jewish Community Survey, a large-scale survey conducted with Jews in Sydney and Melbourne in 2008 and 2017 by Markus and colleagues, included a series of items on antisemitism.…”
Section: Historical Overviewmentioning
confidence: 99%